Preventing Alcohol‐Exposed Pregnancies: A Randomized Controlled Trial of a Self‐Administered Version of Project CHOICES with College Students and Nonstudents. (2nd May 2017) - Sobell, Linda Carter; Sobell, Mark B.; Johnson, Kenneth; Heinecke, Nicholas; Agrawal, Sangeeta; Bolton, Burt
Abstract : Background: Alcohol‐exposed pregnancies (AEPs) are a preventable cause of birth defects and developmental disabilities for which many women are at risk. The initial 5‐session Project CHOICES intervention was found to prevent AEPs. In the ensuing decade, there have been several additional CHOICES‐like studies. This study, Project Healthy CHOICES, had 2 objectives: (i) to compare outcomes for students versus nonstudents; and (ii) to test a self‐administered mail‐based version of the Project CHOICES intervention. Methods: A randomized controlled trial (RCT) compared 2 interventions for women of childbearing age (18 to 44) who were at risk of an AEP: (i) motivational feedback based on Project CHOICES and (ii) information only. Advertisements recruited 354 women (145 college students; 209 nonstudents) at risk of an AEP. Intervention and study materials were available in English and Spanish. Of the 354 women, 44% were minorities (25% identified as Hispanics). Results: At the 6‐month follow‐up, the interventions did not differ and there was no Intervention by Student Study interaction. However, over the entire 6‐month follow‐up, significantly more students (68%) than nonstudents (46%) were not at risk of an AEP (2.1 odds ratio; confidence interval = 1.47 to 2.95). For all groups, risk reduction occurred primarily through effective contraception. Conclusions: There was no significant difference between the 2 interventions. However, over the entire 6‐month follow‐up interval, college students were significantly more likely than nonstudents to not be at risk of an AEP and to use effective contraception. While the student groups had significantly higher reduced risk of AEP outcomes, there was also substantial risk reduction for women in the information only condition. These results suggest that the most effective AEP prevention efforts would be to inform women at risk that they could become pregnant. Because about half of all pregnancies are unplanned, identifying women at risk and preventing the risk of AEPs should be a public health priority. Abstract : This figure compares reduced risk outcomes (reduced alcohol use and/or effective contraception) for preventing alcohol‐exposed‐pregnancies (AEP) for the current study, Project Healthy CHOICES (PHC), and six other CHOICES‐like RCTs (experimental and control groups combined). The highest reduced risk outcomes occurred for students who received a motivational feedback intervention. The results of this study suggest that disseminating low‐cost, informational brochures in health‐care settings where women seek services could prevent AEPs. For college students, effective contraception was the most common prevention strategy.